Isolation of Campylobacter concisus from feces of children with and without diarrhea. - Van Etterijck, R (1996)
A prospective study compared fecal isolation rates of Campylobacter concisus for children with diarrhea and without diarrhea by a filter technique in which media were incubated for 4 days in a microaerobic atmosphere. No statistically significant difference in isolation rates was found (13.2% in patients with diarrhea and 9% in controls). Moreover, 35 of 37 children attending the same day care center harbored different C. concisus strains, as was demonstrated by arbitrary primer PCR DNA fingerprinting. These data suggest a lack of a pathogenic role for C. concisus in enteritis.